An Analysis of Grammatical Errors in French Descriptive Texts of 11th Grade of Fashion Students at SMK Negeri 1 Wonogiri - Andriyana Adhayanti; Ria Fitrasih (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
Vocational high school (SMK) students who face heavy vocational-practice workloads encounter particular challenges in mastering the complex grammatical system of French. This study aims to analyse grammatical writing errors in French descriptive texts produced by 11th Grade of Fashion Design students at SMK Negeri 1 Wonogiri, with a view to identifying morphosyntactic weaknesses and informing more targeted pedagogical interventions. A descriptive qualitative design was adopted, employing an error-analysis method. Data were collected through documentary study of 32 students' written tasks on the theme décrire une personne (describing a person), evaluated against the A1 level standards of the Cadre Européen Commun de Référence pour les Langues (CECRL). Results indicate that students performed best on instruction compliance (87.50%) and basic vocabulary (93.75%), while serious weaknesses were recorded in coherence and cohesion (78.12% low-scorers) and spelling (62.50% low-scorers). The dominant error types included failure to apply gender-agreement rules (accord de genre), omission of accent marks, and absence of cohesive devices, rendering student texts atomistic in nature. These errors are attributed principally to first-language interference from Indonesian, constrained instructional time, and the competing cognitive demands of vocational coursework. The study recommends the adoption of colour-coded visual strategies to teach grammatical gender, alongside scaffolded coherence-building exercises.